Deltamethrin resistance in Ceratitis capitata (Diptera: Tephritidae): Selections, monitoring and effect of synergist. (July 2019) - Lisi Demant, Luciana; Baldo, Fernando Berton; Sato, Mário Eidi; Raga, Adalton; Paranhos, Beatriz Aguiar Jordão
Abstract: The Mediterranean fruit fly, Ceratitis capitata (Wied.) (Diptera: Tephritidae), is considered one of the pests with the greatest importance for fruticulture in the world, causing significant losses to fruit production and limiting the free transit of fruits for exportation. The objectives of this research were to evaluate the potential development of deltamethrin resistance in a Brazilian population of C. capitata ; evaluate a possible metabolic resistance using a synergist, and compare the susceptibility to deltamethrin in populations of C. capitata from different regions of Brazil. The bioassays were performed with adult females via insecticide ingestion. Selection for resistance and susceptibility to deltamethrin with a population of C. capitata [from Campinas, State of São Paulo (SP)], under laboratory conditions, led to a resistance ratio (LC50 R/LC50 S) of 7.23. Deltamethrin susceptibility was evaluated in populations of C. capitata from: Campinas and Pedra Branca, State of São Paulo; Pelotas, State of Rio Grande do Sul; and Petrolina, State of Pernambuco. Differences in the susceptibility to the pyrethroid insecticide were observed among the populations. The population from Pelotas was 26 times more resistant to deltamethrin than the population from Petrolina. Studies with the synergist DEF (SSS-tributylphosphorotriothioate) indicated the involvement of esterases in the resistance of C. capitata to deltamethrin. Highlights: There is variability in deltamethrin susceptibility in Brazilian populations of Ceratitis capitata . A medfly population from Pelotas-RS was 26 times more resistant to deltamethrin than a population from Petrolina-PE. Esterases are involved in deltamethrin resistance in C. capitata .